The presence of endophytic actinobacteria in mangosteen peel (Garcinia mangostana) and its antioxidant activity - Fily Larasati; IRMANIDA BATUBARA; YULIN LESTARI (Society for Indonesian Biodiversity, 2020)
Abstract. Larasati F, Batubara I, Lestari Y. 2020. The presence of endophytic actinobacteria in mangosteen peel (Garcinia mangostana L.) and its antioxidant activity. Biodiversitas 21: 1488-1497. Mangosteen (Garcinia mangostana L.) is a family member of Clusiaceae which is rich in secondary metabolite compounds that can function as antioxidants. Besides being produced by its host plant, the bioactive compounds can also be produced by endophytic actinobacteria. The purpose of this study was to explore the presence of endophytic actinobacteria from mangosteen peel and determine its antioxidant activity. The actinobacteria were isolated, purified, morphologically characterized, molecularly identified, extracted with ethyl acetate and tested for antioxidant properties. The antioxidant activity was assayed using DPPH (2.2-diphenyl-1-picrylhydrazyl) and ABTS (2,2?-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) methods. The components of extracts were separated by Thin Layer Chromatography (TLC) and bioautography was done to determine the antioxidant bands. As a result, five isolates of endophytic actinobacteria in mangosteen peel showed to have difference in aerial mycelium color, substrate mycelium color, and types of spore chains. Based on 16S rRNA gene analysis, AGM3.2 isolate showed similarity with Streptomyces griseochromogenes ATCC 14511 (T) 99.06%. AGM3.1 had similarity with Streptomyces osmaniensis OU-63 (T) 98.35%. Meanwhile, AGM2.3 were similar to Streptomyces xanthophaeus NBRC B-5414 (T) 99.82%, AGM2.2 had similarity with Streptomyces xanthophaeus NBRC B-5414 (T) 98.95%. In addition, AGM2.1 has homology with Streptomyces goshikiensis NBRC 12868 (T) 99.52%. Using both DPPH and ABTS, supernatant of AGM2.1 showed the highest antioxidant activity indicated by 36.96 and 98.80 inhibition, respectively. Antioxidant capacity of ethyl acetate extract of AGM2.1 was 22.22 ?g AEAC/mg extract (DPPH) and 20.34 ?g AEAC/mg extract (ABTS). Meanwhile, ethyl acetate extract of mangosteen peel had antioxidant capacity by 21.17 µg AEAC/mg extract (DPPH) and 18.75 µg AEAC/mg extract (ABTS). Antioxidant bioautographic analysis of mangosteen peel ethyl acetate extract was compared with alpha mangosteen standard. The results showed that alpha mangosteen presence in the mangosteen extract with the same Rf value of 0.64 with standard. Meanwhile, actinobacterial ethyl acetate extract from AGM3.1, AGM2.3, AGM2.2, AGM2.1 each have the same Rf value with the alpha mangosteen standard. However, the spot for alpha mangosteen had dark red color, while spots of the four actinobacterial isolates showed to have blue color indicating different antioxidant compounds. The blue spot indicates the flavone, flavanone, flavonol, and isoflavone. These compounds include a subgroup of flavonoid compounds. Ethyl acetate extract AGM3.2 does not have spot compounds with the same Rf value as the alpha mangosteen standard. Study clearly shows that endophytic actinobacteria from mangosteen peel have potency as antioxidant.